Treatment of inflammatory root resorption using mineral trioxide aggregate: A case report - Roohollah Sharifi; Masoud Parirokh; Seyed Amir Razavi Satvati; Mahmoud Torabinejad (Wolters Kluwer Medknow Publications, 2014)
Introduction: This report presents a case to show inflammatory root resorption can be successfully treated by using mineral trioxide aggregate (MTA). Case Report: A central maxillary incisor of an eight-year-old boy was avulsed associated with crown fracture secondary to a fall. The tooth was stored in ice. Early attempts at pulpal revascularization of the replanted tooth proved unsuccessful. To stop inflammatory root resorption, long-term calcium hydroxide therapy was employed. Despite the use of calcium hydroxide, resorption continued. Subsequent to the failure of that treatment, MTA was used as a root canal filling material. At 20-month follow-up, the tooth was asymptomatic and had clinical signs of ankylosis but external inflammatory root resorption had stopped. Discussion: MTA may be considered as an alternative option for the treatment of continuous external inflammatory root resorption.